Hospitality Students’ Pragmatic Competence in Apology - Stefanus Prima; Dang Arif Hartono; Herry Windawaty (Universitas PGRI Yogyakarta, 2023)
When dealing with guests’ complaints using English language, hospitality frontliners at hotels in Indonesia will also rely on their pragmatic competence to satisfy the guests. This research is aimed at analyzing the strategies used by hospitality students in handling guests’ complaints especially in terms of apologizing and whether there is a significant difference between those with part-time job experience and those without the experience. The study utilized quantitative method by collecting responses (n =22) using Written Discourse Completion Task (WDCT). Using the categorization of apology strategies (Cohen, 1986), the results show that the most frequently used strategies are expressing apology and offering repairs. Other strategies such as admitting responsibility and explaining are used much less frequently, while promise of forbearance was never used. Furthermore, after performing t-test, the 13 participants who took part-time jobs (M = 1.76, SD = 0.25) compared to the nine participants in the control group (M = 1.38, SD = 0.33) demonstrated significantly better at using strategies in apology for handling complaints, t(14) = 2.87, p = .01.